2015
DOI: 10.1182/blood-2015-01-624585
|View full text |Cite
|
Sign up to set email alerts
|

Direct and immune-mediated cytotoxicity of interleukin-21 contributes to antitumor effects in mantle cell lymphoma

Abstract: • IL-21 activates IL-21R-dependent singling to mediate direct cytotoxicity of MCL cells.• Indirect effects of IL-21 on immune effector cells also contribute to antitumor effects against MCL.Mantle cell lymphoma (MCL) is a distinct subtype of non-Hodgkin lymphoma characterized by overexpression of cyclin D1 in 95% of patients. MCL patients experience frequent relapses resulting in median survival of 3 to 5 years, requiring more efficient therapeutic regimens. Interleukin (IL)-21, a member of the IL-2 cytokine f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 50 publications
4
25
0
Order By: Relevance
“…To further evaluate the potential contribution of STAT-3, BAX, and cMyc to fusokine-induced cell death, we performed knockdown of these proteins using specific siRNAs. As previously reported, 32,35 inhibition of STAT-3 completely abrogated IL-21-induced cell death. Although fusokine treatment led to more pronounced death than IL-21, STAT-3 inhibition still completely blocked fusokine-induced cell death, as opposed to control siRNA ( Figure 3C).…”
Section: Acd20-il-21 Fusokine Is More Potent Than Native Il-21supporting
confidence: 61%
See 4 more Smart Citations
“…To further evaluate the potential contribution of STAT-3, BAX, and cMyc to fusokine-induced cell death, we performed knockdown of these proteins using specific siRNAs. As previously reported, 32,35 inhibition of STAT-3 completely abrogated IL-21-induced cell death. Although fusokine treatment led to more pronounced death than IL-21, STAT-3 inhibition still completely blocked fusokine-induced cell death, as opposed to control siRNA ( Figure 3C).…”
Section: Acd20-il-21 Fusokine Is More Potent Than Native Il-21supporting
confidence: 61%
“…[26][27][28][29][30][31] We and others recently showed that IL-21 enhances rituximab-mediated ADCC of NHL cells, including mantle cell lymphoma (MCL) and chronic lymphocytic leukemias. 20,32,33 Similarly, increased ADCC was also observed in a murine breast cancer model treated with the anti-HER2 Ab (trastuzumab) and IL-21. 21,34 Apart from its immunostimulatory effects, IL-21 exerts direct cytotoxicity on a variety of IL-21R-expressing NHLs, including diffuse large B-cell lymphoma (DLBCL), MCL, chronic lymphocytic leukemia, and follicular lymphoma.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations